Common uropathogens and their antimicrobial susceptibility patterns at a tertiary care hospital in Pakistan - Faraz Basharat Khan, Khubaib Shahzad, Nida Basharat Khan , Zaufishan Kokab , Zahoor Iqbal , Khurram Mansoor, Faraz Basharat Khan, Khubaib Shahzad, Nida Basharat Khan , Zaufishan Kokab , Zahoor Iqbal , Khurram Mansoor (Journal of Rawalpindi Medical College, 2020)
Introduction: Urinary tract infections (UTIs) are one of the most frequent infections encountered by doctors. It can be a significant source of morbidity for some patients. Microbes are growing resistant to commonly prescribed antimicrobials and UTIs are becoming more difficult to treat day by day. The study aimed to investigate the common uropathogens encountered in our geographical region and to study their antibacterial susceptibility patterns. Material and Methods: It was a retrospective descriptive study carried out in the Armed Forces Institute of Urology, in collaboration with the Armed Forces Institute of Pathology, Rawalpindi, Pakistan, during the year 2019. Positive reports for urine culture and sensitivity performed during the last two years were studied to document various isolates and their antimicrobial sensitivity. Results: A total of 3191 positive urine cultures in the last two years (2017-2019) were studied. Escherichia coli (66%), followed by Klebsiella Pneumonia (12%) were the most frequently encountered organisms. Overall resistance to Ciprofloxacin was 66%, Cotrimoxazole was 62%, Gentamycin was 40%, Fosfomycin (9.5%) followed by Meropenem (28%) and Nitrofurantoin (35%) were the most sensitive antibiotics. Conclusion: Gram-negative bacilli are the predominant organisms responsible for urinary tract infections. These uropathogens show significant resistance to routinely used antibiotics. Fosfomycin and Nitrofurantoin are suitable oral anti-bacterials for patients with UTI, whereas Meropenem is suitable if an injectable therapy is required. Our study may act as a guide for the choice of empiric antibiotics based on local resistant patterns.